Estrus induction and fertility response in acycling Awassi-Malpura ewes treated with progesterone and PMSG in a tropical climate - DAS, G K; NAQVI, S M K; GULYANI, R; PAREEK, S R; NARULA, H K; MITTAL, J P (The Indian Journal of Animal Sciences, 2014)
Estrus and fertility response were assessed in acycling crossbred Awassi-Malpura ewes (n=46: maiden=23: parous=23) treated with natural progesterone and pregnant mare serum gonadotropin (PMSG). Progesterone (@ 350 mg/sponge) impregnated intra-vaginal sponges were placed in-sitra vagiffa for 12 days followed by an I/m injection of PMSG (@ 200 IU/ewe) at sponge withdrawal. Estrus detection was done using approned ram of proven vigour, at an interval of 6 hr, commencing 24 hr of sponge withdrawal and continued up to 72 hr. A fixed time (52-54 hr after sponge withdrawal) insemination was performed by depositing the diluted semen in both the uterine horns with the aid of laparoscope. The overall estrus response was 80.4% and relatively higher in maiden (91.3%) than parous ewes (69.6%) but difference was not significant. Overall the mean interval to onset was 29.8 hr bit earlier in maiden group than parous while the duration of estrus was longer in former than later group. The mean estrus length was 26.8+- 1.71 hr irrespective of the groups. Overall.44.4% ewes lambed at term on insemination basis whereas lambing rate was slightly better (51.4%) with estrus ewes. Parity does not have any significant influence on lambing outcome. The study indicates that intravaginal progesterone (@ 350 mg) sponge in combination with PMSG (@ 200 IU) can be successfully used for estrus induction in acycling crossbred Awassi-Malpura ewes. A fixed time IUAI at 50-54 hr after sponge withdrawal may result into a reasonable fertility response.